Solution of the Navier-Stokes equations for aerofoils undergoing in-plane oscillations - Shaw, Scott (Cranfield University, 1995)
Although a full simulation of the flow field generated around helicopter rotor blades in forward flight requires consideration of many complex interacting flow phenomena, such a fluctuations in the velocity and incidence of the oncoming flow, three dimensional effects, moving shock waves, shock induced separation and dynamic stall, considerable physical insight may be obtained by removing the influence of many of these phenomena and studying the simplified flows which result. In the present work the problems of moving shock waves and shock induced separation commonly encountered on the advancing side of helicopter rotor blades during forward flight are addressed by examining the behaviour of the flow field around aerofoils undergoing inplane oscillations, of the form M∞ = M(1)(1+µsin(ωt))at constant angles of incidence.